Wide Area Monitoring and State Estimation for a Given Phasor Network - Al-Shah, A. H. (Asian Journal of Science and Applied Technology, 2014)
In this paper, the modeling for a complete scenario of a proposed wide area measurement system (WAMS) based on phasor measurement units (PMUs) technology is presented. The purpose is to increase the overall system efficiency and reliability for all power stages with improved monitoring, protection, and control capabilities of power networks. The developed system is simulated using the Matlab/Simulink program. The power system layer consists of a 500 kW generation station, two transformers, four circuit breakers, two short transmission lines, and two one MW loads. The communication layer consists of four PMUs, located at generation and load buses. The proposed system is tested under two possible cases; normal operation and fault state. It was found that power system status can be easily monitored and controlled in real time by using the measured values online which improves the overall system reliability and avoids cascaded blackout during fault occurrence. The simulation results confirm the validity of the proposed WAMS technology for smart grid applications.